KARAKTERISTIK PERUSAHAAN DAN RASIO KEUANGAN TERHADAP MANAJEMEN LABA - RACHEL RACHEL; Riki Sanjaya (E-Jurnal Akuntansi TSM, 2022)
This study aims to analyze the effect of profitability, financial leverage, firm size, growth, audit quality, firm age, and audit committee on earnings management. This study uses a sample of 588 data from 196 non-financial companies listed on the Indonesia Stock Exchange with the research period during 2017-2019. The sample of this study is the result of purposive sampling technique. The results of this study indicate that there is an influence of profitability, growth, and audit quality on earnings management. Profitability influence to earnings management because occur agency problem which interest of agent different with principal, so agent would show good profitability to achieved e.g bonus; growth influence to earnings management because agent want show their’s growth to stakeholders even with earnings management; audit quality influence to earnings management because big fours KAP witth their’s capability could prevent earnings management. Meanwhile, there is no influence of financial leverage, firm size, firm age, and audit committee on earnings management. This means have implication to stakeholders to consider that factors to prevent earnings management.